Strategi Humas Karang Taruna dalam Meningkatkan Partisipasi Pemuda di Wilayah RW 05 Kota Bambu Utara - Salfhaoctha Friemay Aliefia Poetry; Laili Fithriyah; Bunga Jelita; Ferdiansyah Ferdiansyah; Siti Fatimah Azzachra (Asosiasi Dosen Muda Indonesia, 2025)
Youth participation in social and community activities in urban areas tends to decline along with increasing individualism, personal busyness, and the dominance of digital activities among the younger generation. This condition presents a challenge for youth organizations such as Karang Taruna, which have a strategic role in fostering, empowering, and developing youth potential at the neighborhood level. Therefore, a public relations strategy is needed that can build effective, participatory communication, and is relevant to the character of today's youth. This study aims to determine and analyze the public relations strategy of Karang Taruna RW.5 Kota Bambu Utara in increasing youth participation in organizational and social community activities. This study uses a constructivist paradigm with a qualitative approach and descriptive methods. Data collection techniques were carried out through in-depth interviews with Karang Taruna administrators and the youth involved, and supported by documentation of organizational activities. Data analysis was carried out using the interactive model of Miles and Huberman which includes data reduction, data presentation, and drawing conclusions. The research results show that the public relations strategy of Karang Taruna RW.05 includes the utilization of interpersonal communication, the use of digital media such as WhatsApp and Instagram, as well as a persuasive and participatory approach in conveying messages to youth. This strategy is considered capable of building emotional closeness, increasing awareness, and encouraging youth involvement gradually. Although there are still obstacles such as differences in busyness and low response from some youth, an adaptive and dialogical public relations strategy has proven to play a significant role in increasing youth participation and strengthening the existence of Karang Taruna in the RW.05 environment of North Bambu City.